2021
DOI: 10.3390/d13030104
|View full text |Cite
|
Sign up to set email alerts
|

Cetacean Strandings and Museum Collections: A Focus on Sicily Island Crossroads for Mediterranean Species

Abstract: The study examined the extent of the cetacean strandings in Italy, with a particular focus on Sicily Island. The paper aimed to contribute to the description of a pattern that contemplates the “regular and rare” cetacean species passage along the Sicilian coast. The estimate of marine cetacean strandings was extrapolated from the National Strandings Data Bank (BDS—Banca Dati Spiaggiamenti) and evaluated according to a subdivision in three coastal subregions: the Tyrrhenian sub-basin (northern Sicilian coast), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…In the latter area, the species was considered to prefer the upper continental slope (e.g., Bearzi et al, 2011;Praca & Gannier, 2008;Laran et al, 2010Laran et al, , 2017, with a more recent use reported also of offshore areas (e.g., ACCOBAMS, 2021; Azzellino et al, 2016;Labach et al, 2015), in accordance with the prediction of this study. The species is also confirmed in the Tyrrhenian sea, around the Pontine Archipelago and along the Sicilian coast (Lo Brutto et al, 2021;Mariani et al, 2016). In the Central Mediterranean, the predicted suitable areas in eastern Sicily and in the northern Ionian Sea were in line with the findings of other studies (e.g., Cipriano et al, 2022;Monaco et al, 2016).…”
Section: Main Findings On Speciessupporting
confidence: 88%
“…In the latter area, the species was considered to prefer the upper continental slope (e.g., Bearzi et al, 2011;Praca & Gannier, 2008;Laran et al, 2010Laran et al, , 2017, with a more recent use reported also of offshore areas (e.g., ACCOBAMS, 2021; Azzellino et al, 2016;Labach et al, 2015), in accordance with the prediction of this study. The species is also confirmed in the Tyrrhenian sea, around the Pontine Archipelago and along the Sicilian coast (Lo Brutto et al, 2021;Mariani et al, 2016). In the Central Mediterranean, the predicted suitable areas in eastern Sicily and in the northern Ionian Sea were in line with the findings of other studies (e.g., Cipriano et al, 2022;Monaco et al, 2016).…”
Section: Main Findings On Speciessupporting
confidence: 88%
“…Collections can be important to resolve taxonomic issues and reconstruct distribution patterns of species and evolutionary processes across different time frames and geographical areas [1][2][3]. The investigation of such materials is of particular importance for rare or threatened species, such as large marine or terrestrial carnivores, often stored in old collections [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Here we introduce a dataset of sightings, strandings, and museum records of the species in the Mediterranean Sea, and the first documented Mediterranean records, originating from the southern Tyrrhenian basin. Relevant biodiversity information can be obtained from materials and data collected in the past and preserved in the Natural History Museums, which can provide overlooked and, in many cases, still unpublished data (Tedesco et al, 2020;Lo Brutto et al, 2021). Additionally, the sightings and strandings herein reported highlight the potential role of the citizens' participatory science.…”
Section: Introductionmentioning
confidence: 97%